2022
DOI: 10.3389/fpls.2022.843071
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Induced Cold Tolerance in Plants: Physiological and Molecular Responses

Abstract: Cold stress is one of the most limiting factors for plant growth and development. Cold stress adversely affects plant physiology, molecular and biochemical processes by determining oxidative stress, poor nutrient and water uptake, disorganization of cellular membranes and reduced photosynthetic efficiency. Therefore, to recover impaired plant functions under cold stress, the application of bio-stimulants can be considered a suitable approach. Melatonin (MT) is a critical bio-stimulant that has often shown to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 156 publications
0
20
0
Order By: Relevance
“…Nonetheless, over-expression of MT responsive genes under various abiotic stresses is studied in few crops. Many studies reported that MT levels significantly increased under stress conditions ( Xing et al, 2021 ; Qari et al, 2022 ).…”
Section: Mechanism Of Melatonin Induced Stress Tolerancementioning
confidence: 99%
“…Nonetheless, over-expression of MT responsive genes under various abiotic stresses is studied in few crops. Many studies reported that MT levels significantly increased under stress conditions ( Xing et al, 2021 ; Qari et al, 2022 ).…”
Section: Mechanism Of Melatonin Induced Stress Tolerancementioning
confidence: 99%
“… 10 Studies in plants have shown that MEL regulates plant growth, root morphogenesis, floral transformation, and responses to multiple abiotic stresses, 11–17 including cold stress. 14 , 18 For instance, MEL can alleviate the drought stress of wheat, rapeseed and maize by reducing the malondialdehyde (MDA) contents. 19–21 In Limonium bicolor, wheat, and cotton, MEL improved salt tolerance by enhancing the antioxidant enzyme activities and the content of soluble sugar.…”
Section: Introductionmentioning
confidence: 99%
“…25 In conclusion, MEL has been widely used to improve the tolerance against drought, salt, and cold stress. However, in response to cold stress, most studies have been carried out to identify the MEL-induced stress tolerance mechanisms at physiological and biochemical levels in different crop plants; 14 , 18 still, little is known about MEL-induced cold tolerance in rapeseed. Thus, there was a dire need to evaluate the positive impact of MEL in rapeseed seedlings at molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress also reduces photosynthesis by reducing cell turgor and plants’ access to CO 2 owing to the closure of stomata ( Jaleel et al, 2007 ). One of the major detriments of DS is the production of reactive oxygen species (ROS) that damage the structural integrity of membranes, proteins, and DNA ( Ahanger and Agarwal, 2017 ; Sultan et al, 2021 ; Qari et al, 2022 ; Rehman et al, 2022 ). However, plants have developed different mechanisms to reduce the harmful effects of ROS to protect the stability of cellular structures and improve the yield under DS ( Ahanger and Ahmad, 2019 ).…”
Section: Introductionmentioning
confidence: 99%